Marketıng Strategy Of Tolıre Lake As A Tourıst Destınatıon In Ternate Cıty, North Maluku - Safitri Mustadin; I Gusti Putu Bagus Sasrawan Mananda; I Made Sendra (Cita Konsultindo Research Center, 2024)
This research aims to identify marketing strategies through factors that are strengths, weaknesses, opportunities and threats in influencing the level of tourist visits as well as formulating appropriate strategies to be implemented in increasing tourist visits at the Lake Tolire Tourist Attraction. The method used is qualitative research with thematic analysis techniques. Determining informants in this study used purposive sampling and the technique for determining respondents used Accedential Sampling which involved 100 tourists as respondents. The research results show that the total IFAS score is (2.800) and the total EFAS score is (2.789), which means that the tourist attraction of Lake Tolire is currently in quadrant V, namely in a developing position. Alternative marketing strategies in the SWOT analysis obtained six strategies, Strategy (SO) Exploring Potential and strengthening natural authenticity, historical and traditional values ​​and local community culture as a tourist attraction and optimizing digital promotion of the Lake Tolire tourist attraction. Strategy (WO) Improve the facilities and infrastructure of the Tolire Lake tourist attraction and increase tourism human resources. Strategy (ST) Product Innovation for tourism and the creative economy, and Strategy (WT) Establishing collaboration with Stakeholders.